"Toxic" schools? How school exposures during adolescence influence trajectories of health through young adulthood - Courtney E. Boen; Karen Kozlowski; Karolyn D. Tyson (Elsevier, 2020)
A large body of research identifies the critical role of early-life social contexts such as neighborhoods and households in shaping life course trajectories of health. Less is known about whether and how school characteristics affect individual health and contribute to population health inequality. However, recent scholarship argues that some school environments are so stressful due to high levels of violence, disorder, and poverty that they may be "toxic" to student health, but this hypothesis has not been tested using population data. Integrating insights from the life course perspective and stress process model, we use rich longitudinal data from the National Longitudinal Study of Adolescent to Adult Health (n = 11,382), diverse markers of physiological functioning and psychological well-being, and multilevel regression models to examine whether and how school characteristics shape trajectories of physiological dysregulation and depressive risk from adolescence through early adulthood. Findings reveal that, across multiple measures of physiological functioning and psychological well-being, the social and structural characteristics of schools play an essential role in shaping health risk from adolescence through young adulthood-long after students left school. In particular, indicators of school-level violence and perceptions of safety and school social disconnectedness had especially strong associations with health risk in both the short- and long-term. School socioeconomic composition was also strongly associated with physiological dysregulation in young adulthood, net of individual and neighborhood socioeconomic exposures. Together, findings from this study suggest that school environments can serve as early-life stressors in the lives of young people that unequally shape health trajectories and contribute to broader patterns of health inequality.